Projeto Mirage - Queiroz, Heitor Vasconcelos de [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Fiction is the lie that tells the truth. Fictitious stories are used to portray human conditions and qualities, to generate reflection. Mirage, by metaphor is something that presents itself as very good, but that is not true. Through fiction, and an immersive project involving 360º Video, Virtual Reality and hypnotizing music, seeks out to bring to light information about the negative nature of the internet.
Mirage Project
A ficção é a mentira pela qual se conta a verdade. Histórias fictícias são usadas para retratar as condições e qualidades humanas, para gerar reflexão. Mirage, em português, miragem, por metáfora é algo que se apresenta como muito bom, mas que não é verdadeiro. Por meio da ficção, e de um projeto imersivo envolvendo Vídeo 360º, Realidade Virtual e música hipnotizante, busca-se trazer à tona informações sobre a natureza negativa da internet.
Keywords: Realidade Virtual; Vídeo 360º; Ficção; Internet; Virtual Reality; Fiction